Convergence of Print Media In The Digital Age - R. Soegiharto Soegiharto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2022)
The discussion carried out in this journal was to determine how necessary print media was to switch or converge into digital media. In addition to discussing the causes of the decline in the print media industry, this study also discussed the strategies carried out by several print media companies to transform into digital media. This convergence into digital media was also considered necessary because it supported the Sustainable Development Goals (SDGs), namely maintaining land ecosystems by reducing wood-based paper and environmental pollution due to paper and ink waste.